PENGARUH PENGEMBANGAN KARIR, KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. TELKOM AKSES MEDAN - Eka Putri Istiqomah; Hernawaty Hernawaty; Ramadhan Harahap (Ensiklopedia Education Review, 2021)
This study aims to determine whether career development, leadership and competence partially and simultaneously have a positive and significant effect on employee performance at PT Telkom Access Medan. The data analysis technique used is quantitative method with the help of SPSS version 20.0 program. This study uses multiple linear regression analysis. The population in this study were all employees of PT Telkom Access Medan and a sample of 95 respondents. Primary data collection using a questionnaire. The results showed that career development, leadership and competence partially and simultaneously had a positive and significant effect on employee performance at PT Telkom Access Medan.Keywords: career development, leadership, competence, performance